Physicians' Perceptions and Practices on Metabolic Dysfunction-Associated Liver Disease: An Exploratory Survey - Beshyah, Salem A.; Hafidh, Khadijah A.; Eldukali, Wail A.; Hassoun, Ahmed A.K. (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
There has been a rapid increase in the incidence and prevalence of metabolic dysfunction-associated liver disease (MASLD) in the Middle East and Africa (MEA) regions.We aimed to assess the knowledge and awareness of MASLD among MEA physicians and evaluate their current approach to diagnosing, managing, and referring to MASLD. We used an online survey through a validated questionnaire and a convenience sample of MEA clinicians to examine knowledge, practices, and attitudes regarding MASLD and the barriers to providing care for this condition.A total of 128 clinicians completed the survey. Most were from the Arabian Gulf and the Middle East (72.6%). Most were senior adult endocrinologists; 53.2% of respondents considered the prevalence of MASLD in the general population around 10% or 30%; 28.6% of respondents felt that liver enzymes were sufficiently sensitive to detect underlying MASLD. Most respondents were unsure whether the Enhanced Liver Fibrosis score or Fibrosis 4 score could help to identify those with high risk for advanced fibrosis or cirrhosis (54.5 and 29.1%, respectively, were unsure). Although 83.8% of respondents would refer a patient to a gastroenterologist if they suspect the patient has MASLD, 29.4% do not make referrals. Of concern, 64.5% of participants would unlikely refer a patient to a hepatologist unless liver function tests are abnormal. Respondents identified several barriers to making referrals.Most respondents viewed MASLD as a significant health concern. However, the rates of screening for MASLD were low. A key obstacle in managing these patients was the lack of knowledge regarding MASLD. Regional guidelines and continuing professional development activities should focus on strategies for screening at-risk patients, and evidence-based management practices.
Keywords: metabolic dysfunction-associated liver disease (MASLD); nonalcoholic steatohepatitis (NASH); elastography; Enhanced Liver Fibrosis (ELF); Fibrosis 4 (FIB 4); Middle East and Africa; physicians perceptions